Association between nonstandard work schedules and employees’ self-rated mental health with perceived work stress, work–family conflict and job satisfaction as psychosocial mediators: a national study in China - Wang, Zhan; Zhang, Guangsheng (Frontiers in Psychology, 2025)
BackgroundNonstandard work schedules are prevalent across the industrialized world. While prior research indicates nonstandard work schedules lead to poor mental health, little research has explored the psychosocial pathways underlying the association between work schedule and mental health. This study aimed to fill this gap by testing for the mediating roles of perceived work stress, perceived work–family conflict and perceived job satisfaction in the association between nonstandard work schedules and employees’ self-rated mental health.MethodsUsing a nationally representative sample of data from the Chinese General Social Survey (CGSS) in 2021 (N = 1857), and using the Process v4.1 for SPSS, we examined the association between nonstandard work schedules and employees’ self-rated mental health and estimated the independent and joint mediation effects of perceived work stress, perceived work–family conflict and perceived job satisfaction.ResultsA total of 1857 employees participated in the final analysis. Of these, 1,331 employees (71.7%) work fixed day shifts, 24 employees (1.3%) work fixed night shifts, 206 employees (11.1%) work rotating shifts, 243 employees (13.1%) work irregular schedules and 53 employees (2.8%) work other schedules. Nonstandard work schedule was negatively correlated with employees’ self-rated mental health and perceived job satisfaction, and positively correlated with perceived work stress and work–family conflict (p < 0.001). The independent mediation effects of perceived work stress, perceived work–family conflict and perceived job satisfaction was 17.3, 22.4 and 16.5%, respectively. The joint effect of all three mediators mediated about 36.2% of the relationship between nonstandard work schedules and employees’ self-rated mental health. Sensitivity analyses revealed that rotating shift (p < 0.05) and irregular schedule (p < 0.001) were negatively associated with employees’ self-rated mental health, perceived job satisfaction fully mediated the association between rotating shift and employees’ self-rated mental health, while perceived work stress, work–family conflict and job satisfaction jointly and partially mediated the association between irregular schedule and employees’ self-rated mental health (the joint effect of all three mediators mediated about 42.4% of the relationship).ConclusionPerceived work stress, perceived work–family conflict and perceived job satisfaction mediated the relationship between nonstandard work schedules and employees’ self-rated mental health. The findings advance understanding of the psychosocial mechanisms underlying the association between work schedule and mental health.